Odpowiedzi

Najlepsza Odpowiedź!
2010-02-24T19:32:47+01:00
A)5x+10y = 5(x+2y)
b)4m+4 = 4(m+1)
c)3a-3 = 3(a-1)
d)5xy-x = x(5y-1)
e)-6a²-2a = 2a(-3a-2)
f)6a²-12ab = 6a(a-2b)
g)½xy-½x = ½x(y-1)
h)⅓a²b+ ¹/₉ ab² = ⅓ab(a+ ⅓b)
i)2xyz - 4x²y²z + xyz² = xyz(2-4xy+z)
j)stv² - stv + tv² = tv(sv - s + v)
2010-02-24T19:35:14+01:00
A)5x+10y=5(x+2y)
b)4m+4=4(m+1)
c)3a-3=3(a-1)
d)5xy-x=x(5y-1)
e)-6a²-2a=2a(-3a-1)
f)6a²-12ab=6a(a-2b)
g)½xy-½x=1/2x(y-1)
h)⅓a²b+¹/₉ab²=1/2ab(a+b)
i)2xyz-4x²y²z+xyz²=xyz(2-4xy+z)
j)stv²-stv+tv²=tv(sv-s+v)
2010-02-24T19:37:38+01:00
A)5x+10y = 5(x+2y)
b)4m+4=4(m+1)
c)3a-3=3(a-1)
d)5xy-x=x(5y-1)
e)-6a²-2a=2a(-3a-1)
f)6a²-12ab=6a(a-2b)
g)½xy-½x=½x(y-1)
h)⅓a²b+¹/₉ab²=ab(⅓a+¹/₉b)
i)2xyz-4x²y²z+xyz²=xyz(2-4xy+z)
j)stv²-stv+tv² =tv(sv-s+v)